Cerita Anak berbasis Digital sebagai Upaya Orang Tua dalam Perkembangan Bahasa, Intelektual dan Moral Anak - Yanti, Dewi; Hotimah, Wiwin Husnul; Zulfikar, Zulfikar; Putri, Nafi’ Kharisma; Oktaviani, Diah Ayu; Sidik, Alpin Nur (ABDIMAS Iqtishadia, 2023)
Various cases of child development are rife in society. Cases of child development such as language, intellect, and morals deserve important attention. The lack of acquisition of language and literacy that is appropriate for their age is one of the inhibiting factors in children's development that has an impact on their language, psychology, and morals. The stuttering of technology and the communication media experienced by parents are also other factors. It was on this case basis that the PKM team conducted counseling entitled "Digital-Based Children's Story Counseling as a Parent's Effort in the Language, Intellectual, and Moral Development of Children at the Al-Hidayah Taklim Assembly". The implementation of counseling is divided into three sessions, namely: (1) the provision of knowledge about the types of folklore that exist in digital media; (2) the provision of knowledge regarding the five stages of child development and the selection of readings to develop language, intellectual, and moral education in children; and (3) the provision of knowledge of the steps as parents support the development of child psychology through digital reading media. Through this counseling, it was concluded that many parents were still wrong in parenting children in the developmental aspects of language acquisition and child psychology, but the material presented was positively received. Based on the PKM that has been implemented, parents can start a parenting style for their children's language and psychological development according to the material presented.